Study of soluble solid content in limau madu with capacitive sensing technique / Hudaliyana Ghazali, Rafidah Rosman and Zaiton Sharif - Ghazali, Hudaliyana; Rosman, Rafidah; Sharif, Zaiton (UiTM Press, 2018)
Limau Madu is one of two types of citrus that are widely planted in Malaysia. Prior to being marketed to the end users, the Limau Madu would go through the grading process. Among the criteria for a good grading is the taste. However, testing the taste of Limau Madu non-destructively is often challenging. One of the methods to determine the solid soluble content of Limau Madu non-destructively is capacitance sensing technique. The capacitance is measured at different frequencies for several days. The finding shows that as the longer orange is being kept, the permittivity of the fruit, ɛr declines. In term of frequency, permittivity of Limau Madu is highest at frequency of 10 MHz. However, it is different case with SSC which slightly increased over the course of seven days. The performance of the fruit has better impact at lower frequency.